2021
DOI: 10.1042/bsr20201541
|View full text |Cite
|
Sign up to set email alerts
|

C1QTNF6 regulates cell proliferation and apoptosis of NSCLC in vitro and in vivo

Abstract: Objectives: Lung cancer has been reported as the leading cause of cancer-associated deaths in humans, and its incidence continues to increase in the world. A growing number of studies have shown that dysregulated genes are associated with the occurrence and poor prognosis of a variety of tumors, including non-small cell lung cancer (NSCLC). C1q/tumor necrosis factor-related protein 6 (C1QTNF6), a member of the C1q/tumor necrosis factor-related protein (CTRP) family, has been revealed to play a role in carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The results of our study were consistent with those of other past studies. Wei et al ( Zhang and Feng 2021 ) reported that C1QTNF6 was significantly highly expressed in NSCLC tissues and cells and regulated tumor growth, migration, and apoptosis. Similar results have been reported in Japan (Tamotsu et al) ( Takeuchi et al, 2011 ), in which C1QTNF6 has been implicated in tumor angiogenesis in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study were consistent with those of other past studies. Wei et al ( Zhang and Feng 2021 ) reported that C1QTNF6 was significantly highly expressed in NSCLC tissues and cells and regulated tumor growth, migration, and apoptosis. Similar results have been reported in Japan (Tamotsu et al) ( Takeuchi et al, 2011 ), in which C1QTNF6 has been implicated in tumor angiogenesis in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study were consistent with other past studies. Wei et al [21] reported that C1QTNF6 was signi cantly highly expressed in NSCLC tissues and cells and regulated the tumor growth, migration, and apoptosis. Similar results have been reported in Japan (Tamotsu et al) [22], in which C1QTNF6 has been implicated in tumor angiogenesis with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study reported that CTRP6 expression is increased in ccRCC and is positively correlated with disease stage ( 51 ). A very recent study demonstrated that inhibition of CTRP6 can attenuate cell proliferation, migration, invasion and promote apoptosis in vitro and in vivo in non-small cell lung cancer ( 74 ). However, in a previous study, aberrant C1QTNF6 expression is implicated in terrible prognosis accompanied with damage of cell potential in lung adenocarcinoma ( 75 ).…”
Section: Tumor-related Roles Of the Other Ctrp Family Membersmentioning
confidence: 99%